Menggali Tujuan Pendidikan Dalam Al-Qur'an Dan Hadits - Delvia, Melda; Syafruddin, Syafruddin; Rehani, Rehani (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Education plays a crucial role in the lives of individuals and requires clear objectives that are relevant to the context of everyday life. Educational goals should guide every educational activity to achieve optimal results. However, currently there is a tendency in setting educational goals that prioritizes the achievement of worldly goals such as employment, social status, and position, which often obscures the true meaning of education itself. This research uses a library research approach to collect data and information from various related literature sources. The main findings of this research show that the purpose of Islamic education is to achieve Islamic values sourced from the Qur'an and hadith. This goal is reflected in various verses of the Qur'an, such as the achievement of the pleasure of Allah SWT (QS. Al-Baqarah: 207), piety to Allah SWT (QS. Ali Imran: 102), the implementation of worship (QS. Al-Dzariyat: 56), and the fulfillment of man's role as caliph on earth (QS. Al-Baqarah: 30). Meanwhile, the hadith explains the purpose of Islamic education in terms of the development of knowledge, devotion to Allah, the achievement of goodness, as well as orientation to the afterlife and the development of human potential holistically. This study presents a comprehensive understanding of the purpose of Islamic education in the perspective of the Qur'an and hadith